Spectrophotometric Study of the Interaction of 4,6-Diamino-2-Methyl Mercaptopyrimidine with Iodine and Iodine-Monochloride - Sarma, K.G. (Asian Journal of Chemistry, 2016)
The interactions of 4,6-diamino-2-methyl mercaptopyrimidine with iodine and iodine-monochloride have been studied with visible spectrophotometric method. Charge transfer complexes are formed between the components, as is evident from the appearance of a new band in the spectrum. The stability constants of the C.T. complexes in different solvents (single and mixed) have been determined by utilizing he Benesi-Hildebrand equation. The variations in the stability constants though cannot be properly interpreted, can be attributed to the dielectric constants of the medium.